Quality adjustment in non-spanning markets with variety aversion - Kazuhiko Nishimura (Journal of Economic Structures, 2013)
This paper examines the dynamic process of quality adjustment in cases where the economy lacks a sufficient number of markets for coordinating the level of attributes that configure the qualities of products. It shows that an adjustment process through the development and selection of commodities with different qualities may succeed in achieving efficiency or at least, meet the necessary conditions for efficiency. This is true if the user can identify with the altered product and is unaffected by variety in the commodity. It also holds true when the consumer assesses product variety in a smooth (differentiable) function, but not necessarily so if the assessment is non-smooth regarding the homogeneous state. An unidentifiable case can also be subject to inefficiency as the effort of a small quality adjusting agent becomes attenuated.
Keywords: L15; H23; O33; 330; quality adjustment; adaptive selection; trial and error; variety averse; non-spanning markets; Produktqualität; Konsumentenverhalten; Produktdifferenzierung; Konsumtheorie